Microstructure and photoluminescence of CdS-doped silica films grown by RF magnetron sputtering - Rolo, Anabela G. (2002)
The authors wish to thank Luís Rebouta for the RBS data as well as the electron microscopy staff for providing the use of the Philips CM 20 transmission electron microscope (Châtillon-Montrouge, Paris, France).